The Potential of Salivary Lysozyme Level Examination as Caries Biomarker: A Scoping Review - Albertus Luis Sandro Samosir; Ameta Primasari (TALENTA, 2025)
Salivary lysozyme is an antimicrobial enzyme naturally present in human saliva. It is widely recognized as a potential non-invasive biomarker for the early detection of dental caries, which remains a major global oral health concern. Lysozyme plays a significant role in oral immunity by degrading bacteria cell walls and maintaining microbial homeostasis. Therefore, this scoping review aimed to evaluate the potential of salivary lysozyme as a caries biomarker using PRISMA. The method was based on literature searches conducted in Scopus and PubMed databases between 2013 and 2023. The results showed that there were variations in lysozyme concentration according to caries status, where lower levels were often associated with a higher risk, but increased levels showed an active immune response to bacterial infection. Despite methodological differences among studies, there was association between salivary lysozyme concentration and caries severity, underscoring the diagnostic potential. Due to the non-invasive nature, ease of collection, and biochemical stability, salivary lysozyme examination could be applicable in both clinical and preventive settings. However, larger and standardized studies should be conducted in further studies to validate clinical reliability and diagnostic accuracy.